The Sensitivity and Specificity of Parental Report of Concern for Identifying Language Disorder in Children With Craniosynostosis. Issue 1 (January 2021) - Kilcoyne, Sarah; Rajan, Sindhu Menon; Dalton, Louise; Judge, Andy; Overton, Sarah; Wall, Steven; Johnson, David
Abstract : Abstract: Many factors that may co-occur with craniosynostosis, such as oral structural anomalies, hearing impairment, visual impairment, cognitive difficulties and psychosocial factors, may predispose this population to communication difficulties. At the Oxford Craniofacial Unit, children's speech, language and communication are regularly monitored in accordance with a systematic developmental screening protocol developed by the Speech and Language Therapists in the 4 United Kingdom (UK) Highly Specialized Craniofacial Centers. In addition to routine assessments, when parents attend routine multidisciplinary clinic appointments, they are asked about their child's communication development, and whether they have any concerns. A retrospective review was undertaken of parental concerns about hearing, speech development, behavior, physical development, concentration, school and friendships as indicated by parents on the Oxford Craniofacial Unit Pre-Clinic Questionnaire. The areas of concern were then correlated with the results of a standardized, guided parent questionnaire about children's language development, (Children's Communication Checklist - 2 (CCC-2)), to determine whether parental concern alone is a reliable way of identifying whether patients require further assessment for Language Disorder associated with Craniosynostosis. Participants were parents of 89 monolingual English-speaking children with craniosynostosis (62 male; 27 female), age range four to 13 years (mean age = 8 years 7 months), receiving active care at the Oxford Craniofacial Unit (June 2017-July 2018). Results of the pre-clinic questionnaire indicated that 6% of parents had concerns about their child's communication development. Results of the CCC-2 indicated that 29/89 (32.6%) of children required further assessment for Language Disorder associated with Craniosynostosis. When language difficulties were identified on the CCC-2, only 14% (n = 4/29) parents indicated concern on the pre clinic questionnaire. Results indicated that parental concern about behavior was the most important factor in identifying language disorder ( P = 0.023). Results reinforce that the pre-clinic questionnaire is useful for identifying areas of parental concern. Results also indicate that parental concern alone is not sufficient to identify language disorder, and that further, detailed assessment is warranted. The results are consistent with previously reported links between behavior and language in the general population. Abstract : Supplemental Digital Content is available in the text